Health Literacy in Context-Settings, Media, and Populations - Gill Rowlands (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
To date, most published health literacy research has focused on assessing and improving personal skills and abilities. More recently, a better understanding has emerged of the extent to which these skills and abilities are mediated by environmental demands and situational complexities - the context in which health literacy is developed and applied. This has led to much greater attention being given to ways of reducing the situational demands and complexity in which an individual makes a health decision. This collection of papers examines current progress in understanding health literacy "in context", by improving our understanding of the mutual impact of a range of social, economic, environmental, and organisational influences on health literacy. These papers provide unique and original perspectives on the concept, distribution, and application of health literacy in very diverse populations, offering cultural insights and a clear indication of the impact of social and environmental context on health literacy. These perspectives include an examination of differing national policy responses to health literacy illustrating how policy and practice can (and should) respond to this more complete but complex understanding of health literacy. Other papers look at the application of new digital media and the creative harnessing of popular culture as routes to extend the reach and customisation of communications. These papers also illustrate good progress in the evolution of research in the contexts in which health literacy is developed and applied, as well as signaling some areas in which more research would be useful.